“El esquema corporal en el desarrollo de las relaciones sociales de los niños del nivel de Educación Inicial en la parroquia la Victoria, cantón Pujilí, provincia de Cotopaxi” - Pinanjota Gómez, Pamela Lisbeth (2023)
This research work was oriented to diagnose the importance of the body schema in the development of social relations of the children of the level of Initial Education in the Parish La Victoria, Canton Pujilí, Province of Cotopaxi"; the objective of the investigation is to carry out a diagnosis to determine the incidence that has the body schema in the social relations of the children utilizing the application of instruments of collection of information with what will be proposed alternatives of solution to the social development of the infant. The methodology used was the qualitative approach using field and bibliographic research to collect information. The techniques used in the research are the interview applied to the two early education teachers in each educational institution and an observation form for the children at the early education level, used with twenty children, which consists of an evaluation scale of Yes and No, on the body schema in the development of social relations, which made it possible to identify the strengths and weaknesses based on the present topic. The results obtained from the interview made it possible to identify that there is a lack of knowledge on the part of early education teachers in different educational institutions about the body schema in the development of social relations and about the children; it was determined that they do not manage to develop their cognitive, motor and socio-emotional skills, which leads to a lack of knowledge throughout their academic life.